Optimization of glyoxalation for alkali lignin used as bulking agent in wood - Ang, Aik Fei (2016)
Bulking treatment through the impregnation of low molecular weight phenol formaldehyde (LmwPF) resin is a promising method to enhance the dimensional stability of wood. The development of bulking agent that made of modified alkali lignin, the glyoxalated alkali lignin is crucial to mitigate the concentrations of petrochemical derived phenol and carcinogenic formaldehyde. The objective of this study was to enhance the structural homogeneity and chemical reactivity of alkali lignin through sequential organic solvents fractionation and glyoxalation, and to enhance the dimensional stability of jelutong (Dyera costulata) wood using glyoxalated alkali lignin incorporated with low molecular weight phenol formaldehyde resin as bulking agent. Low molecular weight lignin feedstock was obtained through base catalysed depolymerisation (BCD) treatments from an alkali lignin (OL) with a weight-average molecular weight (Mw) of 11646 g/mol at different combined severity factors. The homogeneity of the OL and BCD treated lignins was altered through sequential fractionation using organic solvents with different Hildebrand solubility parameters i.e. propan-1-ol, ethanol and methanol. The yield of OL and BCD treated lignins dissolved in propan-1-ol (F1), ethanol (F2), and methanol (F3) and their molecular weight distributions and chemical structures were determined and characterized by Gel Permeation Chromatography (GPC), Fourier transform infrared (FT-IR) spectroscopy and 13C-nuclear magnetic resonance (NMR) spectroscopy. The reactivity of the obtained low molecular weight lignin feedstock was then enhanced through glyoxalation using non-volatile and non-toxic dialdehyde, namely glyoxal, instead of formaldehyde. The proportion ratio of glyoxal to sodium hydroxide (NaOH) used in the glyoxalation process was optimised using response surface methodology (RSM) and central composite design (CCD). The glyoxalated alkali lignin (GL) synthesised using the optimum proportion ratio of glyoxal to NaOH was then incorporated with LmwPF resin to prepare bulking agent for wood bulking treatment. Oven dried jelutong (Dyera costulata) wood was evacuated under vacuum and then followed by soaking in 15, 20 and 25% concentrations of GL-LmwPF (67% solid of GL:33% solid of LmwPF based on the total solute content) and LmwPF resins, respectively at ambient temperature for 24 h. The impregnated wood was then curing at 180 °C for 30 min. The resin weight percent gain (WPG) and dimensional stability in terms of antiswelling efficiency (ASE), moisture excluding efficiency (MEE) and water absorption (WA) as well as leachability of bulking agents for GL-LmwPF treated wood were determined and compared with untreated wood and wood treated solely with LmwPF resin. The formaldehyde release for both GL-LmwPF and LmwPF treated wood were also determined. BCD treatments did not increase the yield of an OL dissolved in propan-1-ol or ethanol but did increase the yield of OL dissolved in methanol. Repolymerization of OL occurred during the BCD treatment. Lower molecular weight, more homogeneous OL tended to dissolve in propan-1-ol and ethanol, but their overall soluble lignin yields were low. The OL dissolved in methanol had higher molecular weight, was less homogeneous, and had a bulkier structure than OL dissolved in propan-1-ol or ethanol. 13Carbon-NMR and FT-IR spectroscopy analyses confirmed that F3 in OL exhibits optimum yield and appropriate chemical structures as well as molecular weight distributions for resin synthesis. For glyoxalation of alkali lignin, FT-IR spectroscopy revealed that lower molecular weight of lignin polymers was formed due to the crosslinking of lignin molecules via methylene (CH2) bridges through the condensation reaction. RSM and CCD showed that the reactivity of GL reached highest when optimum amounts of glyoxal and NaOH, i.e., 0.222 and 0.353 mole, respectively, were used in the glyoxalation process. The WPG of GL-LmwPF treated wood was lower than LmwPF treated wood. GL-LmwPF treated wood exhibited positive ASE but the values were lower compared to LmwPF treated wood. The MEE and WA of GLLmwPF treated wood were also inferior than LmwPF treated wood and untreated wood. GL-LmwPF resin was leached from treated wood whereas no leaching was found for LmwPF resin after 3 leaching cycles in distilled water. The formaldehyde release of GL-LmwPF resin treated wood was 25.76% lesser than wood treated with LmwPF resin. Wood treated with 25% GL-LmwPF resin yielded highest ASE value compared to 15 and 20% GL-LmwPF treated wood. Hence, wood treated with 25% GL-LmwPF resin together with external coatings could be used in several end applications such as parquet flooring, paneling and furniture component.